Design of a planar periodic lossy magnetic surface to improve active array patterns with enhanced isolation. Issue 15 (5th October 2018) - Hur, Jun; Byun, Gangil; Choo, Hosung
Abstract : This study proposes the design of the periodic lossy magnetic (PLM) surface with a low profile for enhanced array characteristics. The proposed PLM surface consists of multiple rectangular grooves with equal spacing, and the grooves are filled with lossy magnetic materials to increase the surface impedance between array elements to mitigate the mutual coupling. To verify its feasibility, the authors fabricate a two‐element circularly‐polarised patch antenna array with the PLM surface inserted into the ground plane and measure antenna characteristics in a fully anechoic chamber. The results demonstrate that the PLM surface is capable of reducing the mutual coupling so that the active array patterns can be improved with higher front‐to‐back ratios and lower active reflection coefficients for large steering angles.